2008
DOI: 10.1007/s10490-008-9107-2
|View full text |Cite
|
Sign up to set email alerts
|

Unsustainable varieties of capitalism along the Thailand–Malaysia border? The role of institutional complementarities in regional development

Abstract: This contribution aims to couple national institutional complementarities to issues of regional development and long-term sustainability in Southeast Asia's non-core regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…On the one hand, the traditional project management literature has argued that governments are historically inefficient in carrying out major projects. This stream of research indicates that government policy and appointment of individuals based on political affiliations rather than competence often deprive such projects of the necessary talent and expertise (see also Andriesse and Van Westen, 2009). Consequently, decisions are driven by political rather than economic factors (see also Doganis, 2006;Andriesse and Van Westen, 2009).…”
Section: Government Private Sector and Megaprojects: A Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the traditional project management literature has argued that governments are historically inefficient in carrying out major projects. This stream of research indicates that government policy and appointment of individuals based on political affiliations rather than competence often deprive such projects of the necessary talent and expertise (see also Andriesse and Van Westen, 2009). Consequently, decisions are driven by political rather than economic factors (see also Doganis, 2006;Andriesse and Van Westen, 2009).…”
Section: Government Private Sector and Megaprojects: A Reviewmentioning
confidence: 99%
“…This stream of research indicates that government policy and appointment of individuals based on political affiliations rather than competence often deprive such projects of the necessary talent and expertise (see also Andriesse and Van Westen, 2009). Consequently, decisions are driven by political rather than economic factors (see also Doganis, 2006;Andriesse and Van Westen, 2009). The literature on project development and evolutions has indicated that the incremental and sudden increases in the projected time period are often attributed to a lack of depth in the understanding of project requirements to allow the incorporation of strategic thinking during the planning and implementation process.…”
Section: Government Private Sector and Megaprojects: A Reviewmentioning
confidence: 99%
“…5 These elements of an NBS or a VoC can combine in multiple ways, but only where the elements complement each other to form a coherent logic for economic activity is such a combination likely to attain a degree of stability over time. Here Hall and Soskice ( 2001 ) introduce the concept of institutional complementarity: two or more institutions are complementary if the presence or effi ciency of one increases the returns from or effi ciency of the other(s) (see also Andriesse & van Westen, 2009 ). At the fi rm level, Hall and Soskice ( 2001 ) stress that the interlinkages between the elements of an NBS/VoC reward those fi rms whose strategies have a high degree of fi t with the opportunities and resources provided by the respective NBS/VoC and disadvantage fi rms whose strategies are not aligned with these elements (see also Carney, Gedajlovic & Yang, 2009 ).…”
Section: Study 2: Country-level Influences On Differences In Dmne Codmentioning
confidence: 99%
“…At the fi rm level, Hall and Soskice ( 2001 ) stress that the interlinkages between the elements of an NBS/VoC reward those fi rms whose strategies have a high degree of fi t with the opportunities and resources provided by the respective NBS/VoC and disadvantage fi rms whose strategies are not aligned with these elements (see also Carney, Gedajlovic & Yang, 2009 ). The NBS/VoC approach has seen a growing application, not only to developed but also to developing countries (Andriesse & van Westen, 2009 ;Carney et al, 2009 ;Witt & Redding, 2014 ). Furthermore, the concept of an NBS has spawned a growing literature on cross-national differences in CSR priorities (Jackson & Apostolakou, 2010 ;.…”
Section: Study 2: Country-level Influences On Differences In Dmne Codmentioning
confidence: 99%
“…For example, nations may shape market entry strategies, as well as reduce uncertainty and create stability, for firms competing within favored industries through the use of political resources and capabilities (Meyer, Estrin, Bhaumik, & Peng, 2009). However, institutional influence also may lead to rigidity that may reduce the capacity of firms to react to changing circumstances or attenuate poorly performing strategies (Andriesse & van Westen, 2009;Carney et al, 2009). For example, national cultural dimensions may affect such complex and embedded resources as whether firms behave reactively or proactively, the degree to which they respond to regulatory pressures, and the degree of responsibility they are willing to take for their actions.…”
Section: The Institution-based View Of Developing National Industriesmentioning
confidence: 99%